Track & battlefield - Sailer, S.; Seiler, S. (1997)
Everybody knows that the gap in physical performance between male and female athletes is rapidly narrowing. In fact, in an opinion poll just before the 1996 Olympics, 66 per cent agreed that ``the day is coming when top female athletes will beat top males at the highest competitive levels.'' The most highly publicized scientific study supporting this belief appeared in Nature in 1992: ``Will Women Soon Outrun Men?'' Physiologists Susan Ward and Brian Whipp pointed out that since the Twenties women's world records in running had been falling faster than men's. Assuming these trends continued, men's and women's records would equalize by 1998 for marathons, and during the early twenty-first century for all other distances.